SOLIDARITY IN THE TOURING NARRATIVE OF S.U.U.A.L (SCOOTER UIN ULUL ALBAB) MALANG VESPA COMMUNITY: A CRITICAL DISCOURSE ANALYSIS APPROACH - Yunia Dewi Fathmawati (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2021)
Vespa community is known for its solidarity value and S.U.U.A.L Malang is no exception. The application of this value can be observed from the activities or experiences by the group members. In this research, the touring experience of the community is taken as the data since during the trip, there are some inconvenient moments and unexpected accidents that happen. The concept of solidarity can be traced through how the group members face those moments. In this research, the data are divided into five categories based on the situation: natural obstacles, technical problems, resource limitations, the unexpected accident, and the inconvenient situation. To uncover the solidarity concept of the community, Critical Discourse Analysis (CDA) is applied to the narratives of three narrators which are the group members of S.U.U.A.L. The result shows that among five types of solidarity (cooperation, fairness, altruism, trustworthiness, and considerateness), there are two types that are found in the touring experiences by the group members, namely, fairness and altruism.